2012
DOI: 10.5099/aj120300220
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Ischemic Preconditioning Modulates Oxidative Stress in Rat’s Spinal Cord Ischemic Reperfusion Injury

Abstract: Background: Paraplegia is a major devastating and unpredictable complication of spinal cord ischemic reperfusion injury (SC-IRI). Ischemic preconditioning (IPC) is a procedure whereby a brief episode of non-lethal ischemia to an organ produces protection against subsequent detrimental ischemic-reperfusion insult to that organ. It has been shown that IPC may not only induce a local protective effect, but also induces resistant to ischemic-reperfusion damage in remote organs what is termed remote ischemic precon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…These findings are in accordance with the reports of a study conducted by Yuan and et al, who reported that remote ischemia preconditioning decreases cerebral infarct size, increases the cerebral antioxidative capacity after I/R injury, and decreases the peroxidative damage (Yuan et al 2012). Also, in a study conducted by Bashir et al, it was found that the induction of intestinal RIPC before spinal cord injury ameliorates neurological injuries, via keeping of antioxidative enzymes activity, induced by IR (Bashir et al 2012).…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in accordance with the reports of a study conducted by Yuan and et al, who reported that remote ischemia preconditioning decreases cerebral infarct size, increases the cerebral antioxidative capacity after I/R injury, and decreases the peroxidative damage (Yuan et al 2012). Also, in a study conducted by Bashir et al, it was found that the induction of intestinal RIPC before spinal cord injury ameliorates neurological injuries, via keeping of antioxidative enzymes activity, induced by IR (Bashir et al 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, those patients experience serious complications and impairments, including partial to complete sensory loss, paraplegia, and neurogenic bladder and bowel dysfunction (Morsy et al, 2010). This has been also shown in our labs as well as by other authors in experimental animals exposed to SCI or SCI-ischemia reperfusion (CS-IRI) (Bashir et al, 2012). Secondary injury stage post-SC damage is the major event leading to worsening the SC damage and motor function.…”
Section: Introductionsupporting
confidence: 65%
“…Intestinal ischemic preconditioning promotes local and distant organs protection, as verified by Gho et al 22 in the heart and by Bashir et al 23 in the spinal cord, showing reduction in oxidative stress and inflammation.…”
Section: Discussionmentioning
confidence: 76%